Successful en bloc resection with acceptable cosmesis of a right recurrent giant scalp-orbital AVM causing severe disfigurement: a case report - Karki, Anjan Singh; Shresha, Dipendra Kumar; Sedain, Gopal; Shilpakar, Sushil Krishna (Journal of Society of Surgeons of Nepal, 2021)
Scalp arteriovenous malformation (AVM) accounts for only 8.1% of all AVM cases. These lesions are made up of an abnormal fistulous tangle of tortuous dysmorphic network of vessels “vascular nidus” directly connecting between the feeding arteries and draining veins, without capillary connection, located within the incision subcutaneous layer. With time, these congenital lesions may evolve and enlarge and clinically manifest with variable features. The only effective method of preventing evolution of these malformations is to exclude the lesion completely from the circulation. Involvement of the orbit and face may cause severe facial disfigurement, proptosis, visual obstruction and even facial palsy. These lesions may be complicated by ulceration, infection and profuse bleeding. We present a rare case of 40-year-old female with a recurrent congenital scalp-orbital AVM causing proptosis, visual obstruction on the right eye with severe facial disfigurement. The lesion was successfully excised with acceptable cosmesis and removal of the visual obstruction. A brief literature review, imaging findings and the surgical techniques have been presented.